Historical and Projected Cropland Impacts of Heatwaves in Central Asia Under Climate Change - Tao Li; Fengjiao Song; Jiayu Bao; Philippe DeMaeyer; Ye Yuan; Xiaoran Huang; Tao Yu; Naibi Sulei; Anming Bao; Peter Goethals (Earth's Future)
Abstract Central Asia (CA) is a critical agricultural region, contributing significantly to global food and cotton production, yet it faces increasing threats from extreme heatwaves (HWs) due to global warming. Despite this, the specific impacts of historical and future HWs on CA's cropland remain underexplored. Here, using five bias‐corrected global circulation models from the Inter‐Sectoral Impact Model Intercomparison Project Phase 3b (ISIMIP3b), we present a detailed analysis of CA's cropland exposure to HWs from historical periods (1995–2014) and under three Shared Socioeconomic Pathways (SSP126, SSP370, and SSP585) for 2021–2100. Compared to historical levels, we find that exposure to heatwave frequency could increase by 199% by 2081–2100 under SSP126, while exposure to heatwave duration could rise by as much as 852% and 1143% under SSP370 and SSP585, respectively. Northern Kazakhstan emerges as particularly vulnerable, with the highest exposure levels across scenarios. Interactive effects between climate shifts and land‐use changes are the dominant contributors, accounting for over 50% of total exposure in each scenario. These findings highlight CA's vulnerability to HWs under various climate pathways, emphasizing the urgency of targeted adaptation strategies to protect regional agricultural resilience and, by extension, global food security.